Hierarchical red phosphorus incorporated TiO2 hollow sphere heterojunctions toward superior photocatalytic hydrogen production. (10th May 2022) - Huang, Guiqing; Ye, Wanneng; Lv, Chunxiao; Butenko, Denys S.; Yang, Chen; Zhang, Gaolian; Lu, Ping; Xu, Yan; Zhang, Shuchao; Wang, Hongwei; Zhu, Yukun; Yang, Dongjiang
Highlights: TiO2 hollow sphere with mesoporous structure and high specific surface area could be used as a substrate to deposit red phosphorus. The unique hollow structures improve the light utilization efficiency by multi-scatter incident light. The heterojunction between TiO2 and red phosphorus enhances the charge separation and migration efficiency. Abstract: Solar-to-hydrogen conversion through photocatalysis is a sustainable and promising strategy for storing solar energy. Recently, elemental red phosphorus (RP) with broad light absorption has been recognized as a potential candidate for photocatalytic hydrogen evolution, while challenges remain due to the rapid recombination of photogenerated carriers. In this work, RP modified TiO2 hollow spheres were designed and fabricated through the chemical vapor deposition method. The optimal hydrogen production rate reaching 215.5 μmol/(g h) over TiO2 @RP heterostructure was obtained under simulated solar light irradiation. Experimental results evidenced that the hollow sphere structure and RP light absorber extended light absorption ability, and the heterostructure induced interfacial charge migration facilitated photoinduced charge separation, which benefited the photocatalytic hydrogen production performance.